Pengaruh Model Pembelajaran Problem Based Learning terhadap Hasil Belajar IPAS Siswa Kelas IV SDN Sawah Besar 01 - Sri Handayani; Ikha Listyarini; Bagus Ardi Saputro; Miyarti Miyarti (Journal on Education, 2023)
This study aims to examine the increase in student learning outcomes in class IV SDN Sawah Besar 01 Semarang prior to and following the implementation of the Problem-Based Learning instructional model. The design employed a quantitative experiment, specifically the Pre-Experimental Design with the One-Group Pretest-Posttest Design model. The information obtained via the written examination method is a description test. This investigation will be conducted in class IV of SDN Sawah Besar 01 Semarang. Using the saturated sample technique, the sample consisted of twenty fourth-grade students. The results of this study indicate that the paired sample statistical t-test indicates that there is a difference between the average pretest score of 57 and the average posttest score of 70. From the results of student tests, it can be seen that the posttest average is higher than the pretest average. then Ha is accepted while Ho is rejected. Therefore, there is an average difference between the pre- and post-test scores of fourth-grade students at SDN Sawah Besar 01 Semarang before and after implementing the Problem-Based Learning model.